QARAQALPAQ HÁM BASQA DA XALÍQLAR ÁDEBIYATÍNDA AŃSHÍLÍQ TEMASÍ (Teńiz ańshıları haqqında jazılǵan shıǵarmalar tiykarında) - Azatova, J. (SCIENCE and SOCIETY, 2024)
This article analyzes works written about sea hunters in the literature of Karakalpak and other nations. The theme, idea, composition, plot, presentation of images and artistic psychology of the works were scientifically compared.